Ambiente vivencial de ensino-aprendizagem em gestão de projetos - Carreiro, Eduardo de Lima Pinto (2023)
The complexity of the challenges associated with teaching and learning in project management is evidenced by the growing interest of organizations in this field. This trend is driven by the significant increase in the number of institutions that are adopting project-oriented structures, reflecting a significant shift in business dynamics and the need for effective project management approaches. This transition to project-based structures creates a growing demand for highly qualified professionals capable of effectively managing and contributing to these projects. However, educational institutions face the problem of aligning their curricula with the practical needs of the market, often showing a mismatch between the theory taught and the practice applied. In this context, the central focus of this thesis is to address the following question: How can the challenges of teaching and learning in project management be overcome? In this sense, the aim of the thesis is to develop an experiential learning environment aimed at overcoming the challenges encountered in the teaching and learning process in the area of project management. The thesis is structured in a logical sequence made up of three interconnected studies using the Design Science Research (DSR) method, based on (Dresch et al., 2015). The first study focuses on identifying the challenges in teaching, learning and education in project management, as highlighted in the literature. The second study seeks to understand the perceptions and experiences of students, teachers and managers in the field in relation to project management education. Finally, the third study proposes the development of an experiential teaching-learning environment, specific to the area of project management, with the aim of applying and testing the concepts explored in the previous studies. As a result, a detailed research agenda was proposed for education, teaching and learning in project management. Nineteen crucial challenges were identified, as well as a comprehensive survey of nine key categories: (1) learning; (2) teaching; (3) education; (4) competencies; (5) project management approaches and methodologies; (6) tools and software; (7) solutions; (8) limitations and (9) contributions to educational environments. Finally, a proposal for an experiential project management environment was developed, specifically designed to minimize the discrepancy between theory and practice. Based on this proposal, a business game was developed for the practical application of projects under a hybrid approach, as well as an interactive platform designed to solve theoretical and practical challenges identified in Studies 1 and 2. This thesis also resulted in the creation of three technological products: a technical article (Technical/Technological Product), business simulation software (Software) and a teaching manual for the game (Teaching Material). In addition, the work contributes to achieving the Sustainable Development Goals (SDGs 4, 8, 9 and 10), reflecting its social impact.